Photogenerated charge transfer via interfacial internal electric field for significantly improved photocatalysis in direct Z-scheme oxygen-doped carbon nitrogen/CoAl-layered double hydroxide heterojunction - Wu, Yan (2020)
Semiconductor heterojunctions, widely applied in photocatalytic solar-to-chemical energy conversion, are advantageous for spatially separating photogenerated charge across the heterojunction boundary, inhibiting carrier recombination processes and synergistically accelerating photocatalytic reaction beyond individual components. Herein, a novel type of 2D-2D heterostructure consisting of oxygen-doped carbon nitride (OCN) and ultrathin CoAl-layered double hydroxide (CoAl-LDH) with the aid of hydrogen bonding has been constructed via in situ growth method. The visible-light photocatalytic degradation efficiency of the hybridized photocatalyst is 38 and 239 folds higher than that of pure OCN and pure CoAl-LDH, respectively. This is due to the strong electronic coupling effect in the heterostructured interface, which induces photogenerated charge transfer from CoAl-LDH to OCN and make for the constrction of an interfacial internal electric field (IIEF) between CoAl-LDH and OCN. Based on the experimental evidence and density functional theory calculations, an IIEF-induced direct Z-scheme charge transfer mechanism has been proposed to enhance the extraction and utilization of photoinduced electron and hole in respectively CoAl-LDH and OCN. This work uncovers the nature of charge transfer system based on a 2D–2D heterostructured system, which can be potentially employed in various fields of photocatalysis.